The Year of Installation at Artpool : Installation Project 1998. - Artpool, Budapest; Installation Festival Budapest 1998; Dante (Budapest : Artpool, 1999)
DOC/K/S, Akenaton / ; BMZ, Miklós Zoltan Baji / ; Baracchi, Tiziana ; Baroni, Vittore ; Bell, Lilian A. ; Besant, Derek Michael ; Borawski, David ; Bulatov, Dmitry ; Bunus, Ioan ; Cantsin, Monty ; Capatti, Bruno ; Carretta, Luisella ; Clark, Melissa ; Collins, Patricia ; Cook, Geoffrey ; Curmano, Billy X ; Diotallevi, Marcello ; Dudek-Dürer, Andrzej ; Fierens, Luc ; Fricker, H.R. ; Johnson, James ; Galantai, Gyorgy ; B., István Geller ; Heid, Klaus ; Joe, Emily ; Johnson, James ; Kamperelic, Dobrica ; Kecskés, Péter ; Klivar, Miroslav ; Koller, Julius ; Kulchitsky, Miroslav ; Laszlo, Jean-Noël ; Lindemann, Sabrina ; Garcia, Jacalyn Lopez ; Lumb, Michael ; Maggi, Ruggero ; Máté, Gyula ; McCarthy, Dany ; Melnikov-Starquist, Willi R. ; Miti, Luca ; Mitropoulos, Mit ; Morandi, Emilio ; Nakamura, Keiichi ; Netmail, Peter ; Orimoto Tatsumi ; Patella, Luca Maria ; Rizzi, Alberto ; Robic, Jean-François ; Ronai, Peter ; Rose, Matthew ; Schroth, Mary Angela ; Sega, Lada ; Simon, Baudhuin ; Sperling, Ronald ; Sugar, Janos ; Summers, Rod ; Sutherland, W. Mark ; Tasnádi, József ; Tavenner, Patricia ; Trevisan, Bene ; Ujvárossy, László ; Wardle, Jennifer
Engels
The Year of Installation at Artpool : Installation Project 1998, International Installation Festival 1998, Artpool P60 Art Space, Budapest, 17-31 March, 1998
boek